Microwave-Assisted Synthesis: A Green Chemistry Approach for Drug Cocrystals Synthesis - Puspita, Oktavia Eka; Sulistyowaty, Melanny Ika; Salam, Rudy; Setyawan, Dwi (Science and Technology Indonesia, 2025)
Microwave-assisted synthesis (MAS) presents a promising approach to the formation of pharmaceutical cocrystals, offering notable improvements in solubility, dissolution rate, stability, and bioavailability of active pharmaceutical ingredients (APIs). This review aims to evaluate the potential of MAS as a green and efficient strategy for drug cocrystal synthesis, particularly in comparison to conventional methods such as solvent evaporation, slurry crystallisation, and grinding techniques. A systematic literature review was conducted following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, to ensure a comprehensive selection of relevant studies. The analysis focused on reported synthesis methods, cocrystal formation under microwave exposure, reaction conditions, yields, purity, and scalability outcomes of MAS compared to conventional techniques. This review also highlight current applications, critical synthesis parameters, and challenges such as penetration depth, reaction uniformity, and thermal control. Findings indicate that MAS significantly reduces reaction time, minimizes solvent use, and enhances product purity and yield. Its compatibility with solvent-free or minimal-solvent processes aligns closely with green chemistry principles, making it a sustainable alternative. Furthermore, MAS effectively addresses solubility mismatches and process inefficiencies commonly encountered in traditional methods. The future prospect of MAS lies in its integration with continuous manufacturing, automation, and drug repurposing efforts, which could revolutionize pharmaceutical formulation by accelerating innovation while adhering to environmental and regulatory standards.